ANALISIS LINGKUNGAN PERSAINGAN INDUSTRI (Studi Pada PT. Pura Barutama Divisi Engineering Agricultural Machinery) - Rachel Yessica Anju Marpaung (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the internal and external environment of Agricultural Machinery Engineering Division of PT. Pura Barutama, especially in the environment of industrial competition, and to identify the company’s competitive advantages. The analysis of the industrial competition environment is carried out using Michael Porter's five competitive forces model. This research uses qualitative descriptive method. Of the five competitive forces, the most influential ones are customer's bargaining power and rivalry among existing competitors. The company’s customers, who are mostly governmental agencies, have the power to control prices, specifications, and regulations pertaining to agricultural machinery. In addition, other companies that are financially strong and have their own market share make the company difficult to dominate the whole market of agricultural machinery industry. Newcomer’s threat and supplier’s bargaining power have a moderate effect. The threat of substitute products does not have a major impact on the company since there is a governmental policy which mentions that the procurement of goods and services for governmental institutions must be done through e-Katalog. The company's competitive advantage is on the biomass technology embedded in its products and the responsive and long-lasting after-sales service.Keywords: Agricultural machinery, Porter’s Five Forces, Internal Environment, External Environment, Competitive Advantage